Comprehensive geophysical and geological research for recognition of ochreous sediments in Zabratówka, village near Rzeszów - GOŁĘBIOWSKI, Tomisław; SALA, Dariusz; RATAJCZAK, Tadeusz (Geology, Geophysics and Environment, 2011)
This article presents the results of comprehensive research on ochre sediments from the Zabratówka, village near Rzeszów. Fourteen boreholes were drilled in the investigation area for visualization of geological structures and for collecting ground samples for further laboratory measurements. Geochemical, mineralogical and petrophysical analyses were carried out in laboratory and their results were correlated to prepare a geophysical interpretation model. Preliminary georadar surveys were conducted between boreholes to analyze the possibilities and limitations of this measurement technique used in outlining Carpathian ochre accumulations. Detailed three-dimensional georadar surveys were carried out in the selected area of the research site and the results of geophysical measurements were correlated with the information from boreholes and laboratory tests.